ANXIETY OF MOTHERS BEFORE IUD AND IMPLANT INSERTION - Masruroh, Masruroh; Yuliani, Istri; Mindarsih, Eko; Verawati, B.; Rahmawati, Ida (Nurse and Health: Jurnal Keperawatan, 2024)
Background: Long-Term Contraceptive Method (LTC) is one of the effective efforts to space pregnancies. There is a psychological impact in prospective Intra Uterine Device (IUD) acceptors regarding the side effects that may appear after installation. One of the obstacles that causes women of childbearing age to use the IUD method is because of the level of anxiety, worry, and fear. Objectives: To analyze the characteristics and determine the level of anxiety of mothers who accept IUD and Implant KB. Methods: This research was a descriptive research type. conducted in August-December 2023 at the Isti Yuliani Independent Midwife Practice (PMB). The sample technique in this study used total sampling with 56 respondents. The research instrument with a questionnaire measuring anxiety levels with HRSA with the results of the Cronbach's Alpha test was 0.793 with the number of items 14 items greater than 0.6. The analysis used univariate.. Results: The characteristics of respondents in this study were 100% in the range of Women of Childbearing Age (WCA), the majority completed secondary education as much as 87.5%, had a parity of more than one 80.4%, respondents were unemployed 83.9%, chose the most LTC was IUD 53.6% and the reason respondents came / visited was to remove and at the same time reinstall LTC IUD & Implant. The anxiety in LTC IUD and Implant acceptors before the installation procedure had a mild anxiety level of 42 people (75%) and with a moderate anxiety level of 12 people (21.4%). Conclusion: The characteristics of respondents were the age of respondents in the range of WCA, the majority had secondary education, parity of more than one, the majority were unemployed, the most LTC was IUD and the reason respondents came / visited was to remove and at the same time reinstall LTC IUD & Implant. The majority experienced mild anxiety.